Psychological Safety as an Enduring Resource Amid Constraints - Hassina Bahadurzada; Amy Edmondson; Michaela Kerrissey (Frontiers Media S.A., 2024)
ObjectivesWhile psychological safety is recognized as valuable in healthcare, its relationship to resource constraints is not well understood. We investigate whether psychological safety mitigates the negative impact of resource constraints on employees.MethodsLeveraging longitudinal survey data collected from healthcare workers before and during the COVID-19 crisis (N = 27,240), we examine how baseline psychological safety relates to employee burnout and intent to stay over time, and then investigate this relationship relative to resource constraints (i.e., the inadequacy of staffing and tools).ResultsUsing hierarchical linear models, we find that psychological safety has enduring protective benefits for healthcare workers during periods of stress, and that these benefits mitigate the negative consequences of resource constraints for burnout and turnover intent over time.ConclusionThese findings extend the empirical basis for psychological safety and suggest that investments in building psychological safety can foster employee resilience and organizational commitment, even when resources are strained.